Surgical Technique: Arthroscopic Treatment of Heterotopic Ossification of the Hip After Prior Hip Arthroscopy - Ong, Crispin (Springer-Verlag, 2012)
BACKGROUND: The incidence of heterotopic ossification (HO) after hip arthroscopy reportedly ranges from less than 1.0% to 6.3%. Although open debridement has been described and a few series mention arthroscopic debridement, the techniques for arthroscopic excision of HO have not been described in detail. We describe the arthroscopic treatment of this complication. DESCRIPTION OF TECHNIQUE: Revision arthroscopy was completed in the central and peripheral compartments using prior portals and fluoroscopy was used to identify the HO. Spinal needle localization was used to triangulate onto the HO. Cannulas were inserted over the spinal needle. Once the HO was clearly identified with the arthroscope, it was excised using a burr and confirmed on fluoroscopy. METHODS: We retrospectively reviewed 66 patients who underwent arthroscopic treatment of femoroacetabular impingement between July 2008 and June 2010. There were 36 females and 30 males with an average age of 38 years (range, 15–68 years). Eight of the 66 (12%) patients had HO develop. Using the grading of Brooker et al., six patients had Grade 1, one had Grade 2, and one had Grade 3 HO. Three patients with HO were symptomatic and underwent arthroscopic resection. We obtained modified Harris hip scores (HHS) and radiographs at followup. The minimum followup for the three patients with revision surgery was 2 years (mean, 2 years 2 months; range, 2 years–2 years 8 months). RESULTS: The three patients who underwent arthroscopic resection had HHS ranging from 85 to 96 at last followup. No patient had recurrence of HO. CONCLUSIONS: Our data suggest HO is not uncommon after hip arthroscopy for the treatment of femoroacetabular impingement but most patients have minor degrees and no symptoms. In symptomatic patients, arthroscopic excision appears to relieve pain and restore function.